Towards joint consideration of adaptive capacity and water security: lessons from the arid Americas - Kirchhoff, Christine (2016)
Freshwater resources face enormous pressures to meet human and ecosystem needs in a changing climate. These pressures brought concern for rising water insecurity high on global agendas and, renewed interest in improving water security. This review traces the recent evolution of these efforts including the challenges faced in attempts to enhance water security. In addition, this paper adds a new dimension to water security by proposing a theoretical model that jointly considers interdependencies between water security, adaptive capacity, and adaptive water management. Finally, the review illustrates and critically evaluates these interdependencies using three case studies from the US, Mexico and Argentina, and ends with suggestions for future research.